Different defibrillation strategies in survivors after out-of-hospital cardiac arrest. Issue 23 (14th June 2018) - Zijlstra, Jolande A; Koster, Rudolph W; Blom, Marieke T; Lippert, Freddy K; Svensson, Leif; Herlitz, Johan; Kramer-Johansen, Jo; Ringh, Mattias; Rosenqvist, Mårten; Palsgaard Møller, Thea; Tan, Hanno L; Beesems, Stefanie G; et al.
Abstract : Background: In the last decade, there has been a rapid increase in the dissemination of automated external defibrillators (AEDs) for prehospital defibrillation of out-of-hospital cardiac arrest patients. The aim of this study was to study the association between different defibrillation strategies on survival rates over time in Copenhagen, Stockholm, Western Sweden and Amsterdam, and the hypothesis was that non-EMS defibrillation increased over time and was associated with increased survival. Methods: We performed a retrospective analysis of four prospectively collected cohorts of out-of-hospital cardiac arrest patients between 2008 and 2013. Emergency medical service (EMS)-witnessed arrests were excluded. Results: A total of 22 453 out-of-hospital cardiac arrest patients with known survival status were identified, of whom 2957 (13%) survived at least 30 days postresuscitation. Of all survivors with a known defibrillation status, 2289 (81%) were defibrillated, 1349 (59%) were defibrillated by EMS, 454 (20%) were defibrillated by a first responder AED and 429 (19%) were defibrillated by an onsite AED and 57 (2%) were unknown. The percentage of survivors defibrillated by first responder AEDs (from 13% in 2008 to 26% in 2013, p<0.001 for trend) and onsite AEDs (from 14% in 2008 to 30% in 2013, p<0.001 for trend) increased. The increased use of these non-EMS AEDs was associated with the increase in survival rate of patients with a shockable initial rhythm. Conclusion: Survivors of out-of-hospital cardiac arrest are increasingly defibrillated by non-EMS AEDs. This increase is primarily due to a large increase in the use of onsite AEDs as well as an increase in first-responder defibrillation over time. Non-EMS defibrillation accounted for at least part of the increase in survival rate of patients with a shockable initial rhythm.